Pneumonia as an impediment to treat patients in the early period after stroke - Małodobry, Katarzyna; Juda, Małgorzata; Ozga, Dorota (Journal of Education, Health and Sport, 2018)
Introduction: Infections are a common complication in the treatment of acute stroke. Among them, most often pneumonia, which contributes to increased mortality from stroke, prolong hospitalization, difficulties in care, reduce functional performance improvement and increased cost of treatment. The aim of the work is less analysis of the causes and consequences of the development of pneumonia in the early period after stroke and identify predictors of pneumonia and the need to take preventive measures to prevent the development of disease. Summary: Pneumonia developing in the early period after stroke affects the final outcome and contributes to longer hospitalization, deterioration of clinical status of patients and the results of functional improvement. Current methods to prevent the development of lung zaplenia require the involvement of the entire therapeutic team, which involves a large investment of time and cost of therapy. Therefore, constantly sought are more effective methods of prevention and treatment of pneumonia among stroke patients.